Asymmetric-triazine-cored triads as thermally activated delayed fluorescence emitters for high-efficiency yellow OLEDs with slow efficiency roll-off. Issue 42 (10th October 2016) - Xiang, Yepeng; Gong, Shaolong; Zhao, Yongbiao; Yin, Xiaojun; Luo, Jiajia; Wu, Kailong; Lu, Zheng-Hong; Yang, Chuluo
Abstract : Two asymmetric-triazine triads are demonstrated for the first time as yellow TADF emitters exhibiting a peak external quantum efficiency of 13.0% and an ultra-slow efficiency roll-off of 11.5% at high luminance. Abstract : Two yellow-emissive triads, DPXZ– as -TAZ and TPXZ– as -TAZ, featuring an asymmetric triazine (1, 2, 4-triazine) core as an electron acceptor, phenoxazine units as electron donors and phenyl groups as π-linkages are constructed. Both emitters possess high thermal stability, suitable HOMO/LUMO levels, relatively high PLQY, near-zero singlet–triplet energy splitting, apparent TADF features and short delayed lifetimes. As a result, a yellow OLED utilizing TPXZ– as -TAZ as an emitter reaches a maximum external quantum efficiency (EQE) of 13.0%, which is on a par with a similar device (13.3%) based on a symmetric-triazine (1, 3, 5-triazine) cored analogue. Surprisingly, a TPXZ– as -TAZ-based device exhibits a high EQE of 11.5% and an ultra-slow efficiency roll-off of 11.5% at a high luminance of 1000 cd m −2 . For the first time, this work reports the huge potential of asymmetric triazine compounds as TADF emitters for high-performance OLEDs.